The Co-Biosorption Possibility of Single and Quaternary Heavy Metals by Multi-Metal-Tolerant Bacteria Isolated from Electroplating Effluents - Alhammadi, Eeman; Halimoon, Normala; Zulkeflee, Zufarzaana; Johari, Wan Lutfi Wan (Fine Chemical Engineering, 2025)
This study examined the competitive biosorption of metals in single- and multicomponent solutions and the factors influencing metal removal, such as pH, contact time, biosorbent dosage, and initial metal concentration. It evaluated the properties of co-biosorption and the applicability of copper (Cu), zinc (Zn), nickel (Ni), and chromium (Cr) metal ions from aqueous solutions onto biomass from electroplating effluents under ideal conditions. The study used a single isolate of Kocuria rhizophila and a consortium of three isolates: Bacillus megaterium, Sphingobacterium ginsenosidimutans, and Kocuria rhizophila. Isotherms, kinetics, and thermodynamics were used to analyse experimental data. The findings showed that, at a pH of 6.0 and a biomass dosage of 1.5% (0.9 g/L), the consortium achieved better biosorption conditions than the single biomass. It had values of 33.11 mg/g for Ni and 28.81 mg/g for Cr, while the values were 26.88 mg/g for Ni and 21.65 mg/g for Zn at pH 5.0 and a biomass dose of 2.0% (0.898 g/L) for K. rhizophila. These values were obtained at the same contact time of 50 minutes and a temperature of 37 °C. The Langmuir model accurately predicted the equilibrium data for metals, outperforming other models except for copper with the consortium, which better complied with the Freundlich model. It was also found that the experimental results and the pseudo-second-order kinetic model largely agreed, except for the quaternary system using the consortium, which complied better with the pseudo-first-order model. The results revealed that the biosorption process was spontaneous and endothermic in nature. The biomass consortium of B. megaterium, S. ginsenosidimutans, and K. rhizophila could effectively remove mineral mixtures from electroplating effluent under optimized conditions for bioprocessing electroplating effluents with weak acidity or close to neutral pH at a medium temperature.